1979
DOI: 10.1073/pnas.76.8.4107
|View full text |Cite
|
Sign up to set email alerts
|

Release of platelet-derived growth factor from human platelets by arachidonic acid

Abstract: Platelet a-granules contain a factor that stimulates the proliferation of arterial smooth muscle cells and may play a role in atherogenesis. We have studied the role of arachidonic acid in mediating the release of the platelet-derived growth factor (PDGF) from human platelets. PDGF was assayed by stimulation of [3Hlthymidine incororation into DNA of mouse 3T3 cells. Platelet aggregation and the release of platelet factor 4, P-thromboglobulin, and serotonin were also studied.A biphasic response pattern was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…Platelets play a pivotal role in wound healing by releasing a number of growth factors that can promote angiogenesis (5,7,8,29). Therefore, we hypothesized that, in addition to inhibitory effects on platelet aggregation, antiplatelet drugs might impair gastric ulcer healing by virtue of inhibitory effects on growth factor release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelets play a pivotal role in wound healing by releasing a number of growth factors that can promote angiogenesis (5,7,8,29). Therefore, we hypothesized that, in addition to inhibitory effects on platelet aggregation, antiplatelet drugs might impair gastric ulcer healing by virtue of inhibitory effects on growth factor release.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet aggregation is a cardinal feature of vascular repair. A variety of potent angiogenic stimulators, including VEGF (5), platelet-derived endothelial cell growth factor (6), EGF (7), and platelet-derived growth factor (8), are stored in platelets and released during clotting at the wound. Activation of platelets by ␣-thrombin (9) stimulates angiogenesis in the chick chorioallantoic membrane (10).…”
mentioning
confidence: 99%
“…A variety of bioactive substances, including growth factors and chemokines (Linder et al, 1979;Maloney et al, 1998;von hundelshausen et al, 2001), are stored in platelets and released during activation. Endostatin, a potent inhibitor of angiogenesis (O'Reilly et al, 1997), has been shown recently to be contained within platelets and to be released in response to thrombin but not to ADP (Ma et al, 2001).…”
mentioning
confidence: 99%
“…A variety of other growth factors, including vascular endothelial growth factor, epidermal growth factor and platelet-derived growth factor, are stored in platelet alpha granules and released during platelet aggregation in response to di erent agonists (Linder et al, 1979;Maloney et al, 1998). It is most likely that the release of those factors is due to degranulation during platelet activation and therefore parallels the extent of aggregation (Linder et al, 1979).…”
mentioning
confidence: 99%
See 1 more Smart Citation